THE ROLE OF HUMAN RESOURCES MANAGEMENT FOR CORPORATE SUSTAINBILITY - Nirwana; Haliah; Andi Mutia Lukman (CV. Four Son Scholarship, 2023)
As companies grow, the need for organized and effective human resource management becomes increasingly important. A company's employees are its most valuable resource, which means human resource management (HRM) plays an important role in an organization. Today, companies are becoming increasingly aware of the importance of social, ethical and ecological goals. In addition to financial returns, organizations are setting new goals for themselves, focusing on individual, communal, and environmentally friendly performance and development. In carrying out company operations, it is necessary to realize that there are social impacts that will be caused by the company. So that the responsibility that must be carried out by the company is not only to investors and creditors, but also to the company's social environment. In this case, there is a concept called the Triple Bottom Line that should be applied by every company. This article aims to conduct a literature review on the importance of human resource management in sustainable development to support companies to grow and develop sustainably.